Procedure for Extending Safety Certificates for Coal Carrier Vessels at The Harbor Master's Office and Class 1 Port Authority in PT. Pacific Samudra Sentosa Bandar Lampung - Thezha El Hutapea; Suparman Suparman; Meriah Kita Deliani N (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
This research was created to find out how to carry out the process of extending ship safety certificates that have expired and renewing them in order to comply with policies, standards, norms, guidelines, criteria and procedures as well as technical guidance, evaluation and reporting in the field of shipworthiness, measurement. Ships and ship nationality, nautical, technical and ship radio, pollution and ship health management and maritime affairs. In submitting an application, the shipping company must follow the procedures set by the Directorate of Shipping and Maritime Affairs, sub-directorate of ship safety, with the requirement to attach complete documents such as an application letter, ship safety certificate.